Diversity and regeneration guilds of tree species in an edge of a natural forest in contact with a pinus plantation Diversidade e guildas de regeneração de espécies arbóreas na borda de uma floresta nativa em contato com plantio de pínus - Rosa A.D.* (2015)
The objective of the present study was to verify the influence of edge-effect on diversity and regeneration guilds participation in a forest fragment in contact with a Pinus plantation. For this, the adult (dbh - diameter at breast height≥5 cm) and regenerative (height higher than 15 and dbh<5 cm) components were sampled in five, 20×100 m, transects perpendiculars to the edge of a fragment. Each transect was subdivided in five, 20×20 m, subplots, defining the following sectors representing the edge-interior gradient: 0-20 m, 20-40 m, 40-60 m, 60-80 m and 80-100 m. The species were classified according to the following regeneration guilds: pioneer, light demanding climax and shade tolerant climax. The diversity (Shannon Index) and guilds abundance in each sector were determined. The data were analyzed by Hutcheson t test and proportion test. While no variation was observed for the adult component, the highest of diversity was observed in the edge (0-20 m) for the regenerative component. Variations along the edge gradient of the relative participation of guilds were observed only for adults, with a concentration of Pioneer within the first 40 m.